Analysis of apoptosis in breast cancer patients - Smolarz, Beata; Westfal, Bogdan; Kozłowska, Elżbieta; Romanowicz-Makowska, Hanna; Zadrożny, Marek; Pertyński, T.; Stetkiewicz, T. (Menopause Review/Przegląd Menopauzalny, 2004)
Summary Objective: Apoptosis process (programmed cell death) has been shown to be activated in the majority of cancer tissues. Results from studies that assayed apoptosis in breast cancer samples are reviewed. Materials and method: To study apoptosis activation during the progression of breast cancer, its activation in tissues of various stages of breast cancer was analysed. The levels of the apoptosis status in breast cancer and normal tissues using various molecular genetic methods: electrophoresis methods and the TUNEL assay (terminal deoxynucleotide transferase-mediated deoxyuridine triphosphate (dUTP)-biotin nick end-labeling of DNA fragments) were investigated. Results and conclusion: Several data suggest that the quantitative analysis of apoptosis may play a potential role as prognostic adjuncts for both premenopausal and postmenopausal patients with breast cancer.